The Use of Cashless Payment And E-money in Consumer Behavior for Generation Z in English Village of Pare Kediri - Qomariyah, Nurul; Widuri, Trisnia (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: to know and understand the use of cashless payment and e-money in consumer behavior, consumptive for Generation Z who are in Kampung  English of Pare Kediri. Method: This research uses qualitative and a literature review​ . For making references and especially for child young generation Z who are in the English village of Pare Kediri Findings Research: the use of cashless payments and e-money provides convenience and practicality in doing transactions so which causes behavior consumptive  for Generation Z who are in the village of English Pare Kediri Contribution theoretical / Originality: This research contributes significantly to understanding the connection between using cashless payment and e-money systems in consumer behaviour for Generation Z. The study can identify several theoretical contributions, among them the development theory of consumer behaviour in the digital era. Implications Practitioners / Policies: Practical recommendations are provided for young people, especially Generation Z, who are the actors and targets of sellers to gain profit or results. the implications relate to the understanding and use of cashless and e-money Research limitations: Sample limitations, external and internal factors, advantages or disadvantages of cashless payments, and e-money Keywords: Cashless payment, E-money, Consumer behavior and digital transactions